Three techniques for 360-degree gonioscopy-assisted transluminal trabeculotomy with iTrack advance - Sean Smith; Jessie Wang; Shivani Kamat; Arsham Sheybani; Ian Patterson; Mary Qiu (American Journal of Ophthalmology Case Reports)
Purpose: 360-degree gonioscopy-assisted transluminal trabeculotomy (GATT) is a safe and effective angle-based intervention to lower IOP. Use of the iTrack Advance allows the surgeon to efficiently advance the microcatheter in one continuous motion with a slider, an improvement upon previous techniques in which microcatheters or sutures which had to be manually threaded through Schlemm's canal with microforceps. This report demonstrates three variations in surgical technique for successful 360-degree GATT using the iTrack Advance. Observations: The first technique requires retrieval of the tip of the microcatheter and requires an assistant to hold the gonioprism. The second method also requires retrieval of the tip of the microcatheter, but does not require an assistant to hold the gonioprism. The third technique requires neither retrieval of the tip of the microcatheter nor an assistant for the gonioprism. Conclusions and Importance: The three techniques presented here allow for the completion of a 360-degree GATT using the iTrack Advance without having to manually thread a microcatheter or suture through Schlemm's canal.